Technocamps: Advancing Computer Science Education in Wales - Tom Crick (Proceedings of 10th Workshop in Primary and Secondary Computing Education, 2015)
Computer science education in the UK has undergone substantial scrutiny over the past five years. In particular, from September 2014, we have seen the implementation and delivery of a new computing curriculum in England. However, in Wales -- one of the four devolved nation in the UK -- numerous political, geographical and socio-technical issues have hindered any substantive educational policy or curriculum reform for computer science. This is despite the widespread efforts to address the failings of computer science education in schools since at least 2003 through Technocamps, a pan-Wales university-based schools outreach programme.In this paper we outline the history (and pre-history) of Technocamps, contextualised by the devolved nature of education in the UK, positioning Wales with its specific issues and challenges. Furthermore, we present evidence both in support of this university engagement and intervention model as well as its wider positive effect on promoting and supporting computer science education in Wales, a nation about to take its first steps on the path of a large-scale national curriculum review and significant educational reform.